Pelatihan dan Workshop Foto Human Interest untuk Siswa SMA Kolese de Britto, Yogyakata - Setyowati, Endah; Sigalingging , Hendra; Seliari, Tutun (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
The conducted Community Service Program (PkM) aims to provide capacity building for students of Kolese De Britto High School, Yogyakarta, through a workshop on creating human interest photography. Moreover, this human-interest photography workshop is also intended as a means of building students' awareness and empathy on the issues raised by the photo objects themselves. The workshop is designed in a participatory learning approach by using Student Centred Learning (SCL) to create a democratic learning atmosphere. The approach is applied in a session-based program which consists of (1) providing some knowledge about the social and cultural history of the city of Yogyakarta in the context of human-interest photography; (2) technical knowledge in using both cell phone cameras and manual cameras; and (3) an exercise in finding objects and taking photos. To evaluate the student works and its curation, the SMART and SUPER A method is used. The result of the workshop is a module of training guides and a catalogue of student works that can be used for students’ art exhibitions. === Program Pengabdian Kepada Masyarakat (PkM) yang dilaksanakan bertujuan untuk memberikan peningkatan kapasitas bagi siswa-siswi SMA Kolese De Britto, Yogyakarta, melalui lokakarya pembuatan fotografi human interest. Selain itu, workshop fotografi human interest ini juga dimaksudkan sebagai sarana untuk membangun kepedulian dan empati siswa terhadap isu-isu yang diangkat oleh objek foto itu sendiri. Workshop ini dirancang dengan pendekatan pembelajaran partisipatoris dengan menggunakan metode Student Centered Learning (SCL) untuk menciptakan suasana belajar yang demokratis. Pendekatan ini diterapkan dalam bentuk program berbasis sesi yang terdiri atas (1) pemberian pengetahuan tentang sejarah sosial dan budaya kota Yogyakarta dalam konteks fotografi human interest; (2) pengetahuan teknis penggunaan kamera ponsel dan kamera manual; dan (3) latihan mencari objek dan mengambil foto. Untuk mengevaluasi karya-karya siswa dan kurasinya, digunakan metode SMART dan SUPER A. Hasil dari lokakarya ini adalah sebuah modul panduan pelatihan dan katalog karya siswa yang dapat digunakan untuk pameran seni rupa siswa.